The Dalmatian Manuscripts in Beneventan Script and the Notion of “Adriatic Periphery”. Notes for a New Research Setting - Elba, Emanuela (ASPICE HUNC OPUS MIRUM: zbornik povodom sedamdesetog rođendana Nikole Jakšića, 2020)
The analysis of the corpus of manuscripts in Beneventan script from Dalmatia (2011) makes it possible to identify some specific features that characterize the book production in the region over time. The conclusion is that the manuscripts of Dalmatia should not be considered simply as “provincial” products, i.e. lacking the qualitative elements of the artistic production of the major centres, but are instead the result of a complex process of reception, adaptation, reworking of the models, which did not come to an end within a few decades, but lasted until the 13th century. The article aims to take stock of the issue, defining the critical parameters useful to frame the Dalmatian book production through a different interpretative system and a new historiographical approach that finds an effective “theoretical” support in the paradigm of so-called “peripheral art” developed by Lj. Karaman in 1963.